Interdependencia entre la restauración ecológica y la conservación natural (2011)
Ecological restoration is perceived by many conservationists, and by the majority of economists, as a diversion, an illusion, and much worse, as a loss of time and money. In this work we point out that the restoration, in fact, not only complements the conservation of nature but is also useful to achieve a socio-economically sustainable and equitable development. This because to restore and to increase the natural capital base is the best way to generate jobs, and it improves the means of survival and quality of life for all, the same for the economy.